Aprendizaje organizacional y comportamiento ambiental en la industria maquiladora del norte de México - Ma. del Rosio Barajas Escamilla (El Colegio de la Frontera Norte, 2006)
The principal goal of this paper is to analize the environmental performance related with the industrial upgrading in the in-bond industry. The key questions are: a) what are the levels of environmental performance in maquiladoras? and b) Is the environmental performance according with the industrial upgrading? Our hypothesis suggests that the capacity and necessity of applying environmental activities is associated with the industrial upgrading. The construction of technoproductive levels and the environmental performance index identified the sociotechnical aspects compared with our key variables.